Bovine Arboviruses in Culicoides Biting Midges and Sentinel Cattle in Southern Japan from 2003 to 2013. Issue 6 (19th January 2015) - Kato, T.; Shirafuji, H.; Tanaka, S.; Sato, M.; Yamakawa, M.; Tsuda, T.; Yanase, T.
Summary: Epizootic congenital abnormalities, encephalomyelitis and febrile illnesses in cattle caused by arthropod‐borne viruses (arboviruses) are prevalent in Japan. Causative viruses including orthobunyaviruses, orbiviruses and rhabdovirus are thought to be transmitted by Culicoides biting midges. Recently, the incursions of several arboviruses, potentially Culicoides ‐borne, were newly confirmed in Japan. However, their spread pattern and exact vector species are currently uncertain. Attempts to isolate arboviruses from Culicoides biting midges and sentinel cattle were conducted in Kagoshima, located at the southernmost end of the main islands of Japan, a potentially high‐risk area for incursion of arboviral diseases and outbreak of endemic ones. Seventy‐eight isolates comprising Akabane, Peaton and Sathuperi viruses of the genus Orthobunyavirus of the family Bunyaviridae, bluetongue virus serotype 16, D'Aguilar virus, Bunyip Creek virus and epizootic haemorrhagic disease virus serotype 1 of the genus Orbivirus of the family Reoviridae, a potentially novel rhabdovirus of the genus Ephemerovirus and unidentified orbivirus‐like viruses were obtained from Culicoides biting midges and sentinel cattle between 2003 and 2013. Akabane, Sathuperi, D'Aguilar and Bunyip Creek viruses were selectively isolated from Culicoides oxystoma, suggesting this vector's responsibility for these arbovirus outbreaks. The results of virus isolation also implied that C. tainanus, C. jacobsoni and C. punctatus are competent for the transmission of bluetongue virus serotype 16, Peaton virus and epizootic haemorrhagic disease virus serotype 1, respectively. Our monitoring in Culicoides biting midges and sentinel cattle detected the circulation of Akabane virus just prior to the accumulations of bovine congenital abnormalities and encephalomyelitis by it around study sites in 2003, 2006, 2008 and 2013. Silent circulations of the other arboviruses, including potentially new viruses, were also detected during the study period.